Electrochemical behaviour of the MA8 Mg alloy in minimum essential medium. (15th May 2020) - Gnedenkov, A.S.; Lamaka, S.V.; Sinebryukhov, S.L.; Mashtalyar, D.V.; Egorkin, V.S.; Imshinetskiy, I.M.; Zavidnaya, A.G.; Zheludkevich, M.L.; Gnedenkov, S.V.
Graphical abstract: Highlights: Corrosion activity of the MA8 Mg alloy in two physiological solutions is studied. Protective ability of films formed on Mg alloy in MEM and 0.83% NaCl is analyzed. Bilayer structure of the corrosion film formed in MEM on the MA8 alloy is revealed. Ca/P-containing products are the main precipitates on MA8 alloy exposed to MEM. Three stages of the corrosion film evolution for MA8 alloy in the MEM are shown. Abstract: The difference of the protective properties of the corrosion film formed on the MA8 Mg alloy in the mammalian cell culture medium (MEM) and 0.83 wt. % NaCl solution is established using OCP, PDP and EIS tests. The impedance modulus in the frequency range from 10 5 Hz down to 10 −1 Hz for the sample immersed in MEM is higher than that for the sample immersed in NaCl solution. Ca and P rich deposits are formed in the corrosion layer on the Mg alloy in MEM. The model of the corrosion mechanism for MA8 Mg alloy in the MEM is proposed.